Age, BMI, and Medical History as Determinants of Infertility in Women of Reproductive Age - Kurniawati, Erna Yovi; Hidayat, Syarief Thaufik (Fakultas Kesehatan Masyarakat Universitas Pancasakti, 2025)
Infertility is a complex, multifactorial condition influenced by various biological and lifestyle-related risk factors. This study aimed to examine the association between age, body mass index (BMI), and medical history with infertility among women of reproductive age. A cross-sectional analytical study was conducted among 180 women of reproductive age attending primary and secondary healthcare facilities in Yogyakarta and Central Java. Data were collected through structured interviews, anthropometric assessments, and medical record verification. Variables included age, BMI, relevant reproductive medical history (e.g., PCOS, thyroid disorders, endometriosis), and fertility status. Bivariate analyses and binary logistic regression were employed to identify significant predictors of infertility. The prevalence of infertility was 38.9%, with primary infertility comprising 62.9% of cases. Age ≥35 years (OR = 4.71; 95% CI: 2.10–10.57), abnormal BMI (OR = 3.97; 95% CI: 1.81–8.71), and reproductive-related illnesses (OR = 4.23; 95% CI: 1.97–9.08) were independently and significantly associated with infertility (p < 0.001 for all). These factors impair fertility through mechanisms involving hormonal dysregulation, metabolic imbalance, and chronic inflammation. Advanced maternal age, BMI deviations, and reproductive comorbidities are critical determinants of infertility among women of reproductive age. This study underscores the urgency of individualized fertility care within reproductive health strategies. Longitudinal and biomarker-based studies are recommended to further elucidate causal pathways and incorporate male infertility parameters.